The Effects of Institutional Investors Herding on the Performance of Iran Capial Market Anomalies - mohammad hassan ebrahimi sarveolia; Meysam Amiri; Amir Hossein Erzae; Hossein Saeedi (فصلنامه بورس اوراق بهادار, 2022)
Anomalies in financial markets, which is produced and exacerbated by sensitive and imitative behavior and reduces market efficiency, have always been the focus of researchers. In this research, a criterion for measuring the mass turnover of institutional investors is introduced, which, while considering the fundamental factors, also controls the turnover between institutional investors of same type and non-same type. In this study, in order to achieve the above objectives, modeling of institutional investor transactions and deriving mass aggregation criteria from regression models, taking into account the effects of economic variables affecting stock prices, has been used to calculate the aggregate measure. Then, the effects of bulk on momentary anomalies, stock turnover ratio, price volatility, P/E, accrual and profitability to stock return ratio were studied. The results indicate that herding has the greatest effect on momentums. The two-month momentum has the highest coefficient with a negative sign. This means that with the increase (decrease) in bulk density, the two-month momentum decreases (increases), in other words, the increase (decrease) in bulk density leads to a decrease in the abnormal efficiency caused by the momentum. Among the other anomalies examined, the six-month price fluctuation has the greatest impact on mass production. Also, by examining the relationship between bulk density and anomaly, it was determined that this relationship is two-way and also after entering the bulk factor in the Fama-French models, the explanatory power of the model has improved.